2020
DOI: 10.1002/aenm.201903225
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Catalytic Dynamics Through a Crystal Structure Modulation of Bimetallic Catalyst

Abstract: The surface of solid catalysts is one of the most important factors where the interface with reaction products governs the reaction kinetics. Herein, the crystal phase of palladium–copper nanoparticles (PdCu NPs) is controlled to modulate their surface atomic arrangement, which will govern the growth dynamics of discharge products on their surfaces and thus the catalytic performances in non‐aqueous lithium–oxygen (Li‐O2) batteries. First‐principles calculations and experimental validations reveal that homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…It was observed that the phase of PdCu NPs could affect the type and growth behavior of the discharging products of Li-O 2 batteries. [52] Specifically, the DFT calculations and experimental results revealed that the unconventional bcc PdCu can induce homogeneous nucleation and growth of the discharging products (LiO 2 ) with a Frank-van der-Merwe mode on the surface of bcc PdCu electrode, in which LiO 2 can be easily decomposed during the charging process. However, as for the conventional fcc PdCu NPs, LiO 2 tends to form clustered and segregated Li 2 O 2 agglomerates, which show less reversibility and can block the reactive sites on the fcc PdCu electrode (Figure 1h).…”
Section: Metal-air Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the phase of PdCu NPs could affect the type and growth behavior of the discharging products of Li-O 2 batteries. [52] Specifically, the DFT calculations and experimental results revealed that the unconventional bcc PdCu can induce homogeneous nucleation and growth of the discharging products (LiO 2 ) with a Frank-van der-Merwe mode on the surface of bcc PdCu electrode, in which LiO 2 can be easily decomposed during the charging process. However, as for the conventional fcc PdCu NPs, LiO 2 tends to form clustered and segregated Li 2 O 2 agglomerates, which show less reversibility and can block the reactive sites on the fcc PdCu electrode (Figure 1h).…”
Section: Metal-air Batteriesmentioning
confidence: 99%
“…As a result, compared to the fcc PdCu, the bcc PdCu electrode exhibited a much lower overpotential and higher discharging capacity of 12 677 mA h g −1 at 100 mA g −1 (Figure 1i). [52] Reproduced with permission. [32] Copyright 2017, Royal Society of Chemistry.…”
Section: Metal-air Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these non-precious catalysts only show single catalytic activity for the OER or ORR, and the development of high-efficiency bifunctional catalysts is actually challenging and essential for the practical application of Li–O 2 batteries. 53–55 At present, various strategies including surface modification, 56–58 strain engineering, 59,60 phase modulation 61–63 and heterostructure construction have been explored to realize the bifunctional ability for Li–O 2 catalysis. 64–66…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] However, they still face many problems before practical use, such as high charging overpotentials, poor cycle stability, low columbic efficiency, etc. [26][27][28] The researchers phase modulation [61][62][63] and heterostructure construction have been explored to realize the bifunctional ability for Li-O 2 catalysis. [64][65][66] Among them, the heterostructures have be intensively investigated, which are usually defined as composite structures composed of interfaces formed by different solid materials in a broad sense, including conductors, insulators and semiconductors.…”
mentioning
confidence: 99%